2021
DOI: 10.1016/j.ultsonch.2021.105497
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the relationship between particle size and ultrasonic treatment during the synthesis of metal nanoparticles

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 32 publications
5
24
0
Order By: Relevance
“…The increase in the size of S 1.5 can be associated with the grafting of the CS on the SPIONs [56] . In addition to the findings of Yang et al, [57] which recently demonstrated that the use of ultrasonic irradiation of different power ranges between 0 and 500 W can decrease the size of nanoparticles exponentially with an increase in ultrasonic power, our result shows at minimum sonication period mono-dispersed CS coated SPIONs with a narrow size distribution can be prepared as shown in Fig. 5 B.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The increase in the size of S 1.5 can be associated with the grafting of the CS on the SPIONs [56] . In addition to the findings of Yang et al, [57] which recently demonstrated that the use of ultrasonic irradiation of different power ranges between 0 and 500 W can decrease the size of nanoparticles exponentially with an increase in ultrasonic power, our result shows at minimum sonication period mono-dispersed CS coated SPIONs with a narrow size distribution can be prepared as shown in Fig. 5 B.…”
Section: Resultssupporting
confidence: 84%
“…2) The refinement of the SPIONs during the grafting process by the acoustic cavitation process is another aspect that might enhance the magnetization. Recent studies have revealed that the ultrasonic irradiation's power and time can influence the purity, particle size, and particle refinement of the products [57] , [61] . Although CS is a diamagnetic material which supposed to affect the M s of the CS coated SPIONs, our result shows that the ultrasonic irradiation influenced the final M s of the as-synthesized samples.…”
Section: Resultsmentioning
confidence: 99%
“…The contact of particles can reduce the total surface area in the aggregation process resulting in overall energy reduction. Ultrasonication can encourage surface tension between the species caused by the acoustic radiation force on a compressible particle [ 26 ]. The effect of PEG addition on the particle size can be explained by the well-known properties of surfactants including polyethylene glycol to be adsorbed on the particles or seed crystals that decrease their surface energy and prevents aggregation [ 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are many studies on nanoparticules that have gained great attention in the last decade due to their unique properties [15][16][17]. In vivo and in vitro studies have shown that nanoparticules have toxic effects on living things [15,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The solubility values of the metal salts[16] Comparisons of metal salts based on +2 metal cations are as follows, but the anion salts with the highest solubility are salts with Ni 2+ metal cations, and the anion salt group with the lowest solubility is salted with Cu 2+ metal cation.…”
mentioning
confidence: 99%